Primary Periphyseal Stress Injuries of the Fingers in Adolescent Climbers: A Critical Review. Issue 12 (December 2022) - Jones, Gareth; Johnson, Rowena; Schöffl, Volker; Schöffl, Isabelle; Lutter, Chris; Johnson, Mark I.; Halsey, Tim
Abstract: The worldwide rise in popularity of climbing and development of climbing as a competitive sport is reflected by its debut at the 2021 Summer Olympic Games in Tokyo. Digital primary periphyseal stress injuries in adolescent climbers may pose a significant risk to long-term skeletal health. The aim of this article is to critically review research on the diagnosis and management of primary periphyseal stress injuries of the fingers in adolescent climbers. We adopted a systematic approach to searching for relevant literature. Articles were identified after searches of the following electronic databases: Discover, Academic Search Complete, PubMed, Embase, SPORTDiscus, and ScienceDirect. Conclusive evidence suggests digital primary periphyseal stress injuries are a consequence of repetitive microtrauma. Pain reported by adolescent climbers on the dorsal aspect of the proximal interphalangeal joint should be investigated promptly to avoid serious negative consequences. Clinicians should be aware of the efficacy of imaging techniques to inform a clinical diagnosis. A conservative management approach is preferred but in rare cases surgical intervention may be necessary. A diagnostic and therapeutic algorithm for digital primary periphyseal stress injuries is presented.